Neuropsychiatric aspect of social isolation following a lockdown: A perspective - Shreshth Khanna; Ayush Jain; Bhupinder Singh Kalra (Wolters Kluwer Medknow Publications, 2021)
Coronavirus disease 2019 pandemic spreads through inhalation of aerosols or droplets. Therefore, the use of face masks, alcohol-based sanitizers, and most importantly practicing quarantine/ isolation and social distancing are the main modalities for its prevention and control. Although isolation is essential, various psychological effects have been implicated with its practice in most of the age groups. Longstanding isolation and negligible interpersonal interactions can have changes in psychological processes and neurological and morphological changes in the brain. Morphological changes as seen through the neuroimaging studies include reduced volume of the structures involved in the synthesis of various nerve growth factors leading to impaired neurogenesis and subsequently psychological changes which can manifest as mood alterations such as anxiety, depression, feeling demoralized, obsessive thinking, and altered sleep-wake cycles besides others especially, in the vulnerable age groups such as children and the elderly. Although quarantine remains the cornerstone to contain the spread of the pandemic, its psychological impact run simultaneously, which should be, understood, and addressed to ameliorate its long-term impact.